First record of mitochondrial genome of Scincella reevesii (Squamata: Scincidae) and phylogenetic analysis - Jun Zhong; Kun Guo; Li Ma (Mitochondrial DNA. Part B. Resources, 2021)
We sequenced and annotated the nearly complete mitochondrial genome (mitogenome) of Scincella reevesii (Squamata: Scincidae). This mitogenome was 14,106 bp in size and encoded 13 protein-coding genes, two ribosomal RNA genes, and 22 transfer RNA genes. The most common start codon is ATG, the most common termination codon is TAA and five genes have incomplete termination codon T. The overall nucleotide composition was 32.0% of A, 14.3% of G, 26.1% of T, and 27.6% of C. The data will increase the basic information of Scincidae phylogenetic research and can help to better understand the phylogenetic status of S. reevesii in Squamata.